Characterizing Podcast Services: Publishing, Usage, and Dissemination - Gunawardena, Dinan; Karagiannis, Thomas; Proutiere, Alexandre; Vojnovic, Milan (Proc. of ACM IMC 2009, 2009)
In this paper, we aim at characterizing podcast services both from publishers' and users' perspectives, and at analyzing the implications of these characteristics on the design of efficient dissemination systems. Specifically, our goal is to characterize how podcasting content is generated and published, and how users subscribe and consume podcasts. We are also interested in understanding whether podcast episodes are efficiently disseminated to users just using a sporadic direct access to the Internet (which is the current way of downloading podcast episodes), or whether the use of peer-to-peer mobile device-to-device dissemination systems could help enhancing the performance of podcast services. Our study is based on traces of podcast episode releases, subscriptions, and play times from major podcast service providers. An extensive analysis of the traces allows us to develop a comprehensive model of current podcast services, and provides statistics about the type and content of the typical podcasts, the size and the release frequencies of their episodes, as well as their popularity. By studying podcast usage, we show that the service is delay-tolerant, as users may well play podcast episodes a long time after their actual release. An interesting consequence of this delay tolerance is that mobile device-to-device dissemination systems would not be very useful for the current typical podcasts, while they may become more attractive for future interactive podcast services.